I'm not bossy, I'm the boss [compact disc] - O'Connor, Sinéad (Nettwerk, 2014)
The tenth studio album from Sinead O'Connor is passionate and direct with an overarching fragility. It also shows that her voice is as powerful as it is tender. Included among the tracks is Take Me to Church, which made its premiere on NPR.